Effect of Body Habitus on Radiation Dose during CT Fluoroscopy-Guided Spine Injections. Issue 5 (September 2014) - Viola, Ronald J.; Nguyen, Giao B.; Yoshizumi, Terry T.; Stinnett, Sandra S.; Hoang, Jenny K.; Kranz, Peter G.
This study investigated the degree to which body habitus influences radiation dose during CT fluoroscopy (CTF)-guided lumbar epidural steroid injections (ESI). An anthropomorphic phantom containing metal oxide semiconductor field effect transistor (MOSFET) detectors was scanned at two transverse levels to simulate upper and lower lumbar CTF-guided ESI. Circumferential layers of adipose-equivalent material were sequentially added to model patients of three sizes: small (cross-sectional dimensions 25×30 cm), average (34×39 cm), and oversize (43×48 cm). Point dose rates to skin and internal organs within the CTF beam were measured. Scattered point dose rates 5 cm from the radiation beam were also measured. Direct point dose rates to the internal organs ranged from 0.05–0.11 mGy/10mAs in the oversized phantom, and from 0.18–0.43 mGy/10mAs in the small phantom. Skin direct point dose rates ranged from 0.69–0.71 mGy/10mAs in the oversized phantom and 0.88–0.94 mGy/10mAs in the small phantom. This represents a 180–310% increase in organ point dose rates and 24–36% increase in skin point dose rates in the small habitus compared with the oversize habitus. Scatter point dose rates increased by 83–117% for the small compared to the oversize phantom. Decreasing body habitus results in substantial increases in direct organ and skin point doses as well as scattered dose during simulated CTF-guided procedures. Failure to account for individual variations in body habitus will result in inaccurate dose estimation and inappropriate choice of tube current in CTF-guided procedures.